The Villagers’ Emotion in Establishing Harmonious Relationship in Tanjung Pauh and Kumun Villages - Agung Iranda; Siti Raudhoh; Ema Krisnawati (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
The conflict between Tanjung Pauh Mudik and Kumun villages is an issue which continuously acquires a lot of attention of many groups as it causes a lot disadvantage, either death, traumatic experiences, losing homes or properties. After the conflict, the villagers tried to rebuild their life and their village. Rebuilding something destroyed after the traumatic event need positive emotion as a foundation. This research intends to examine more deeply on how these two villagers’ emotions are, especially in an attempt to create harmonization on both villages and their people. Next, to explore the positive consequence of those emotions which impact positively on the villagers in creating peace among them. This research uses the Indigenous psychology approach, with qualitative method through surveys and interviews on the villagers from both villages. The number of the participants ini this research were 86 participants living in Kumun and Tanjung Pauh village. The result of this research shows that the emerged emotions which arise when the villagers would like to create a harmonious relationship are empathy, love of peace, solidarity, the feeling of prosperous and conducive and there is still a feeling of scared. The factors influenced these emotions are the affiliation need, religions, cultures, losing experiences during the conflict, as well as socio-economy. From those results, the researchers concluded that the villagers’ emotions are conditional meaning that when the escalation of the conflict exists people should be able to realize the necessity of love and peace feeling